EFFECT OF THE AQUEOUS EXTRACT OF JUSTICIA INSULARIS T. ANDERS (ACANTHACEAE) ON OVARIAN FOLLICULOGENESIS AND FERTILITY OF FEMALE RATS - TELEFO, Bruno P; TAGNE, Simon Richard; KOONA, Olga Elodie Sandrine; YEMELE, Didiane Mefokou; TCHOUANGUEP, Felicite Mbiapo (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Justicia insularis T. Anders (Acanthaceae) is a medicinal plant whose leaves and those of three other plants are mixed for the preparation of a concoction used to improve fertility and to reduce labour pains in women of the Western Region of Cameroon. Previous studies have demonstrated the inducing potential on ovarian folliculogenesis and steroidogenesis of the aqueous extract of the leaf mixture (ADHJ) of four medicinal plants (Aloe buettneri, Dicliptera verticillata, Hibiscus macranthus and Justicia insularis) among which the later represented the highest proportion. This study was aimed at evaluating the ovarian inducing potential of J. insularis in immature female rats. Various doses of the aqueous extract of J. insularis were daily and orally given, for 20 days, to immature female rats distributed into four experimental groups of twenty animals each. At the end of the experimental period some biochemical and physiological parameters of ovarian function were assayed. The administration of the aqueous extract of Justicia insularis significantly induced an early vaginal opening in all treated groups (P < 0.001) as well as an increase (at doses of 50 or 100 mg/kg) in the number of hemorrhagic points, Corpus luteum, implantation sites, ovarian weight, uterine and ovarian proteins. Ovarian cholesterol level (P < 0.05) significantly decreased in animals treated with the lowest dose (12.5 mg/kg). The evaluation of the toxicological effects of the extract on pregnancy showed that it significantly increased pre- and post-implantation losses, resorption index and decreased the rate of nidation as well as litter’s weight. These results suggest that the aqueous extract of Justicia insularis induces ovarian folliculogenesis thus justifying its high proportion in the leaf mixture of ADHJ.